Passive aggressive personality disorder – behavioral pattern – two cases report - Masiak, Jolanta; Eugene, Andy (Current Problems of Psychiatry, 2011)
Passive aggressive (negativistic) personality disorder lost its position in three clusters of disordered personalities in DSM IV. This was due to controversies connected with dimensions, co-occurrences, and prevalence of this personality disorder in the general popula-tion. In clinical practice, this type of disturbed personality remains an important problem. In our practice, prevalence of this disordered personality or its features seems to be quite significant. Somatic disorders commonly diagnosed in patients with passive aggressive personality disorder are one of common methods of manipulation and should explain their negativistic approach that commonly veil the clinical symptoms of these patients. Common problems connected with the described personalities are abnormal structures of families commonly functioning without a father, as it was taken place in both described patients. Overprotective mothers were not able to estab-lish the upbringing forms that could correct the disturbed development of the personality of the patients. They accepted parasitic-claiming way-of-life of their children. Moreover, in this case, the mother of described girl accepted inversion of their circadian rhythm and as a result functioning of the patient in the growing social isolation.